2018
DOI: 10.1080/13557858.2018.1432752
|View full text |Cite
|
Sign up to set email alerts
|

Culturally-tailored interventions for chronic disease self-management among Chinese Americans: a systematic review

Abstract: Culturally-tailored interventions that incorporate surface and deep structural elements of culture are sensitive and generally effective for Chinese Americans to improve access to health care, disease awareness, social environment, and participants' ability to practice self-management skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…Most of the culturally tailored interventions were conducted in community based settings with experienced bilingual nurses, bilingual community health care providers, or trained multicultural community health workers (Goris et al, 2013). One review reported that interventions were delivered by hired interpreters to aid communication between health care providers and ethnic minority participants (Huang & Garcia, 2018). The aims of interventions were congruent to enhance ethnic minorities’ improvement of care.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the culturally tailored interventions were conducted in community based settings with experienced bilingual nurses, bilingual community health care providers, or trained multicultural community health workers (Goris et al, 2013). One review reported that interventions were delivered by hired interpreters to aid communication between health care providers and ethnic minority participants (Huang & Garcia, 2018). The aims of interventions were congruent to enhance ethnic minorities’ improvement of care.…”
Section: Resultsmentioning
confidence: 99%
“…Seven reviews reported on disease knowledge as a primary outcome of culturally tailored interventions with ethnic minority participants (Goris et al, 2013; Hawthorne et al, 2010; Heo & Braun, 2014; Huang & Garcia, 2018; Joo, 2014; Renzaho et al, 2010; Zeh et al, 2012). This outcome was measured for cancers, HTN, diabetes, or prediabetes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies of hypertension self-management have improved BP outcomes in the Western societies,15 21 22 however, the evidence for hypertension self-management is absent in the Chinese population. A recent systematic review identified only two quasi-experimental studies focusing on hypertension self-management in a population of American Chinese23; much of the evidence was derived from a single urban site so is not representative of individuals living in community settings 24 25…”
Section: Introductionmentioning
confidence: 99%